Analysis of The Implementation of The Cirebon City Regulation on Local Taxes and Local Fees - Patmawati Patmawati; Siti Khumayah (International Journal Labs, 2026)
Local Own-Source Revenue (Pendapatan Asli Daerah/PAD) is a key fiscal component of a region, as it reflects the socioeconomic conditions of the community as well as the region's growth and self-reliance. In an effort to increase PAD, the Cirebon City Government issued a new policy regarding local tax and retribution rates through Cirebon City Regional Regulation (Peraturan Daerah/Perda) No. 1 of 2024. However, the implementation process has not proceeded as anticipated; social unrest has emerged as a result of the substantial increase in Land and Building Tax (Pajak Bumi dan Bangunan Perdesaan dan Perkotaan/PBB-P2), which reached 1,000% and has been perceived as an excessive burden on the community. This study aims to analyse the implementation of this policy using William N. Dunn's policy evaluation theory, which encompasses six criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The methodology employed is qualitative descriptive, utilising direct observation, documentation, and interviews with the Regional Revenue and Finance Agency (Badan Pengelolaan Keuangan dan Pendapatan Daerah/BPKPD) and taxpayers. The research results indicate that this policy effectively increased local own-source revenue (PAD) by 20.09% in 2025; however, it remains suboptimal with respect to the criteria of responsiveness, accuracy, and equity. Challenges in implementation also persist in relation to effectiveness, adequacy, and efficiency. In response to escalating social unrest, the local government ultimately revised the regulations pertaining to PBB-P2 by the end of 2025. It is recommended that the government increase the intensity of public outreach, ensure equitable access to technology, and strengthen the competencies of implementing staff in order to balance fiscal interests with public welfare, and that a formal complaint-handling mechanism be established to serve as a basis for periodic policy improvements.